Homelessness and Socioeconomic Conditions - Punyasavatsut, Arunee (Asia Social Issues, 2025)
The COVID-19 pandemic has led to an increase in homelessness in numerous countries, including Thailand. The economic downturn, particularly the rise in unemployment, largely caused this increase. This study examines the factors influencing homelessness by estimating an equation identifying the determinants of homelessness rates. The independent variables considered in the analysis include the unemployment rate, minimum wage, average household expenses, land appraisal price, average years of schooling, mean O-NET test scores, the proportion of the elderly population, the proportion of patients with schizophrenia, the proportion of people with disabilities, the proportion of COVID-19 patients, the proportion of patients with alcoholism, urbanization rate, maximum temperature, and precipitation levels. The study utilizes cross-sectional data from various provinces in Thailand for the year 2022. The regression analysis, conducted using the ordinary least squares (OLS) method, reveals that increases in average household expenses, the proportion of the elderly population, and the proportion of COVID-19 patients are positively associated with higher homelessness rates. Conversely, a rise in the average years of schooling, indicative of a higher overall education level, is correlated with a decline in homelessness rates. The research results suggest that policymakers should implement plans for enhanced support systems for individuals facing challenges during crises such as infectious disease outbreaks.